Pengaruh Likuiditas, Profitabilitas, Solvabilitas terhadap Returun Saham Pada Masa Pandemi Covid – 19: - Vivi Oktaviana Peso; Gendro Wiyono; Pristin Prima Sari (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
“The Fundamental Influence of Bank Finance Companies on Stock Returns during the Covid-19 Pandemic (study of T-shirts at National Private Banks for the period 2018-2022) listed on the Indonesia Stock Exchange. Aims to answer problems regarding the Effect of Current Ratio, Debt to Equity and Return on Assets on Stock Return of Bank Financial Companies during the Covid-19 pandemic. In this study, the method used was a quantitative approach. The population in this study were 30 National Private Bank Companies. Sampling was carried out using a non-probability method and the sampling technique was purposive sampling. The data were analyzed using the IBM SPSS application. The results of the study show that the Current Ratio (X1) variable has a significant effect on Stock Return (Y), as evidenced by the results of the t test, which is obtained from the t arithmetic value of 2,566 > t table 1.729 and Significant 0,013 < from 0,05. Then the variable Debt To Equity Ratio (X2) has no significant effect on Stock Return (Y) as evidenced by the results of the t test, which is obtained from the t-count value of -809 < 1.729 and significant 0.422 > 0,05. And the Return on Assets (X3) variable has no effect on Stock Return (Y), as evidenced by the results of the t test, which is obtained from the t value of 1,270 < 1,729 and significant 0,209 > 0,05. And from the results of the F test, it is proven that the Curent Ratio (CR,) Debt to Equity Ratio (DER), and Return on Assets (ROA) have a simultaneous effect on Stock Return (Y). Keywords: Current Ratio, Debt to Equity Ratio, Return on Assets, Stock Return